A phase II study of bendamustine in combination with rituximab as initial treatment for patients with indolent non-follicular non-Hodgkin lymphoma. Issue 4 (2nd April 2016) - Luminari, Stefano; Goldaniga, Maria; Cesaretti, Marina; Orsucci, Lorella; Tucci, Alessandra; Pulsoni, Alessandro; Salvi, Flavia; Arcaini, Luca; Carella, Angelo Michele; Tedeschi, Alessandra; Pinto, Antonello; Stelitano, Caterina; et al.
Abstract: The purpose of this phase 2 study was to determine the activity and safety of six cycles of bendamustine and eight rituximab (RB) as first-line treatment of adult patients with advanced stage non-follicular indolent non-Hodgkin lymphomas (INFL). The primary end-point was the complete response rate (CRR) with expected CRR of 75%. Sixty-nine patients were enrolled; median age was 65 years (45–75), 65% were male, 93% of patients had stage IV disease. Complete and overall response rates were 48% (95% CI = 35.6–60.2) and 86% (CI = 75.0–92.8). The most common grade 3/4 adverse events were neutropenia (43%), thrombocytopenia (7%) and anemia (4%); whereas the rate of febrile neutropenia was very low (3%). At a median follow-up of 22 months (1–43 months), 2-year progression-free survival was 89% (CI = 79–95) and 2-year overall survival was 96% (CI = 87–99). RB combination is active and well tolerated in patients with advanced stage previously untreated INFL.